Pembelajaran Bahasa Indonesia pada Komunitas Sekolah Rumah (Homeschooling) - Siddiq, Muhammad (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This thesis aims to gain an understanding the process of the Indonesian language learning in the homeschooling community Klub Oase. This is done by understanding the human aspect, the concept of learning, and the learning systems at Klub Oase. This research is classified in the type of descriptive qualitative  study with ethnographic methods. Through this research, it is known that the Klub Oase is a family community that founded in the basis of a family friendship. Klub Oase trying to keep the identity of the community that is the hallmark of informality, which also became a counter model from the practice of homeschooling that is generally known to the public by learning patterns like formal and informal education. Most members of the Klub Oase agreed that children need a space to grow naturally. Education aims is understood as facilitating all childs potential not to drive the ability to incorporate various things that are considered important and determined by an adult. Most members of the Klub Oase tend to interpret the Indonesian language as a vehicle for social interaction, so that the learning process is done in an integrative manner, natural, and eclectic approach to develop skills of listening, speaking, reading and writing skills through the project, presentations, discussions, games and more which optimize the use of information technology. For members of the Klub Oase, homeschooling children have the opportunity to explore the world around it, because the place to learn are not constrained by the bulkhead wall or a particular building. So that they can